INTERPRETATION OF WILLIAM SHAKESPEARE'S “SONNET 18” THROUGH SEMANTIC ANALYSIS - Aidil Syah Putra; Audia Triana; Az Zahra Rizani (Media Inovasi Pendidikan dan Publikasi, 2024)
Poetry is a type of literary work in which the author expresses their feelings and message primarily through language. Poems employ words that have deeper, more nuanced meanings in addition to their literal ones. This is particularly true of William Shakespeare's